(untitled) (Global Journal of Science Frontier Research, 2024)
Yam Dioscorea spp is a vegetable of great economic and social importance cultivated in tropical and subtropical regions It is a staple food for millions of people especially in West Africa valued for its tuberous roots rich in carbohydrates proteins vitamins and minerals In addition to its nutritional value yam has cultural and medicinal significance used in ceremonies and therapies In Angola climatic and geographic diversity favors the cultivation of different yam genotypes resulting in a genetic heritage that is crucial for crop resilience and food security The morphological characterization of genotypes allows the identification of varieties with desirable attributes such as disease resistance productivity and nutritional quality facilitating genetic improvement programs This study aims to morphologically characterize yam genotypes from different geographic origins in Angola contributing to the knowledge and conservation of genetic diversity and the development of sustainable agricultural strategies Accessions were collected in the provinces of Cabinda Cuanza Norte Cuanza Sul Malange U ge and Huambo including Dioscoreaesculenta Dioscoreaalata Dioscoreacayenesisand Dioscoreabulbifera After collection the materials were documented with detailed information obtained from interviews with local producers The accessions were planted at Fazenda Esperan a in the province of Hu la from August 2022 to October 2023 in a completely randomized experimental design with 15 replications of each species totaling 60 plants Management practices included irrigation staking and manual weeding The morphological characterization was carried out after six months of planting evaluating 22 descriptors of the aerial parts of the plants and after 11 months the tuber characterization was carried out in the Laboratory of the Institute of Agricultural Research in Hu la Data analysis revealed significant variability in plant characteristics All accessions had alternate leaves with 50 having sagittate leaves 25 lobed leaves and 25 chordate leaves The majority of accessions 75 did not have leaf lobes Regarding petiole length 65 had petioles between 5 and 10 cm predominantly green 65 The majority of accessions 61 67 had a distance between the insertion of the petiole on the leaf and the upper end greater than 4 cm Regarding tubers 71 67 of accessions had underground tubers with 31 67 elongated 43 33 oval and 25 irregular Statistical analysis showed significant differences between yam species in all morphometric characteristics evaluated with Dioscoreabulbifera standing out with the highest average values for most of these characteristics